Flow patterns, velocity distributions and mixing time in stirred tank reactor under a range of operating conditions / Nor Haslina Abdullah - Nor Haslina, Abdullah (2020)
The present work employed a two-dimensional Particle Imaging Velocimetry (PIV) technique to determine the flow patterns and velocity distributions of a down-pumping pitched-blade turbine (4PB) and a Rushton turbine (RT) in a flat-bottom fully baffled stirred vessel (T=0.155m) using distilled water and glycerin as liquids. Fluid velocities increased as the impeller speed increased from 50rpm to 300rpm for both fluids and the RT impeller reached a maximum value of velocity of 1.42m/s at the blade tip. The 4PB had higher velocity compared to RT in glycerin, but RT had higher velocity than 4PB in distilled water. In water, radial flow generated from RT discharge that projects the fluid towards the tank wall was stronger than tangential flow from the 4PB. Additionally, it was found that the velocity distribution in distilled water was 69% higher compared to glycerin. As the clearance reduced from T/3 to T/6, the velocity at the blade tip increased because T/3 have well distribution of upward and downward flow while the downward flow tends to circulate faster at T/6. Interestingly, the increased of distance between impeller and measurement point led to decrease in the difference of velocity values between RT and 4PB. RT projected the fluid radially that create high momentum forming upward and downward flow almost evenly while 4PB is dominated by the tangential motion at the blade discharge in distilled water. 4PB tends to have radial motion at the blade tip towards the tank wall in glycerin. Mixing time studies confirm the trend shows by the impeller in the velocity distribution and flow pattern measurements.